An Analysis of Fundraising Strategies In Local Maritime History Museums - McCallum, Matthew Clement (My University, 2014)
Fundraising is an essential part of non-profit organizations like museums. Despite the vast literature that discusses fundraising strategies, there is no literature showing how fundraising strategies are used in maritime history museums. This study focuses on three maritime museums, the Columbia River Maritime Museum, Harbor History Museum and Northwest Maritime Center, to discover themes that may go beyond the broad fundraising literature and give maritime museums more specific data on the strengths, weaknesses, opportunities, and threats associated with their fundraising strategies. Results identified themes including assets in the form of local stories and history, as well as potential business-related ventures; issues related to staffing; and needs focused on donor acquisition, donor retention and community engagement. Overall this study showed that the key strategies identified in fundraising best practices literature is represented in the three museums used in this study. Furthermore, this study provides a resource specific to maritime museums that can aid in how maritime museums approach fundraising.
Thesis (Master's)--University of Washington, 2014
Keywords: Advancement; Development; Fundraising; Maritime; Museum; Museum studies; museology